GIS-material for the archaeological project: Ramshäll - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to construction of a residential block, the Swedish National Heritage Board's contract archaeology division, UV Öst, has performed an excavation of parts of a settlement area close by a well-known cup mark site, RAÄ 188 in Ramshäll, Linköping city. The area contained remnants both from the Neolithic and and from the transition between Late Bronze Age and Early Iron Age. Among the neolithic remains, a longhouse and a pit with plentiful of finds, such as ornamented pottery, were documented. A fragmentary longhouse and several distinct hearths and cooking pits from the Late Bronze Age were also found. After the completed excavation, UV Öst and the County Administrative Board see no hindrance to the planned development. The archaeological site does however continue outside the development area, and its total extent is thus not known.

Purpose:

The information in the purpose is translated from the archaeological report:
The main aim of the excavation was to interpret, document and date the structures and different phases of settlement within the settlement area.

The ZIP file consist of GIS files with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Inför uppförandet av ett nytt stjärnhus för bostäder har Riksantikvarieämbetet UV Öst undersökt delar av ett boplatsområde invid en känd skålgropshäll, RAÄ 188 vid Ramshäll i Linköpings stad. Området visade sig rymma lämningar efter två tidsperioder; dels lämningar från neolitikum samt från övergången yngre bronsålder till äldre järnålder. Bland lämningarna från neolitikum dokumenterades ett rektangulärt långhus samt en mycket fyndrik grop med ornerad keramik. Från slutet av bronsålder härrör ett ofullständigt långhus samt flera distinkta härdar och kokgropar. Efter utförda undersökningar anser UV Öst i samråd med Länsstyrelsen att det inte finns hinder för de planerade exploateringarna. Fornlämningsområdet är emellertid inte begränsat till den exploaterade ytan utan fortsätter utanför denna, vilket innebär att dess totala utbredning ännu inte är känd.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Den huvudsakliga målsättningen var att tolka, dokumentera och datera förekommande bebyggelseskeden och strukturer inom boplatsområdet.

ZIP-filen innehåller GIS-filer med innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Ramshäll
Keywords: Neolithic; neolitikum; Early Iron Age; äldre järnålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi